2018
DOI: 10.1039/c8cp00611c
|View full text |Cite
|
Sign up to set email alerts
|

MRI relaxivity enhancement of gadolinium oxide nanoshells with a controllable shell thickness

Abstract: Gadolinium oxide-based core-shelled nanoparticles have recently emerged as novel magnetic resonance imaging contrast agents for high relaxivity and tumor targeting. However, their relaxivity enhancement mechanism has not yet been clearly understood. We prepared highly dispersible and uniform core-shell structured nanoparticles by encapsulating silica spheres (90 nm in diameter) with gadolinium oxide shells of different thicknesses (from 1.5 nm to 20 nm), and proved experimentally that the shell thickness has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…A study by Yin et al produced silica nanoparticles coated in a Gd 2 O 3 nanoshell of varying thicknesses. By systematically changing the thickness of the silica shell, the variations in relaxivity values could be investigated and demonstrated that a thinner shell resulted in larger r 1 values [47].…”
Section: Paramagnetic Nanoparticlesmentioning
confidence: 99%
“…A study by Yin et al produced silica nanoparticles coated in a Gd 2 O 3 nanoshell of varying thicknesses. By systematically changing the thickness of the silica shell, the variations in relaxivity values could be investigated and demonstrated that a thinner shell resulted in larger r 1 values [47].…”
Section: Paramagnetic Nanoparticlesmentioning
confidence: 99%
“…Nonetheless, ultrasmall NPs have been found to create aggregates in the cerebrum; as a result, it can be said that the toxicity of the particles is proportional to the maximization of the image potency. Yin et al [ 103 ] developed gadolinium oxide-coated silica nanostructures by exploring different thicknesses of the component. It was demonstrated by varying the thickness of the silica shell over a wide range that with thinner shell values, larger r 1 values can be achieved.…”
Section: Gd and Mn-based Nanomaterialsmentioning
confidence: 99%
“…More importantly, because of their structural flexibility, Gd 3+ ‐ and Mn 2+ ‐based nanoparticle systems are more suitable for the design of stimulus‐responsive contrast agents. [ 29,40,45 ]…”
Section: Theory For Preparation Of Stimulus‐responsive Contrast Agentsmentioning
confidence: 99%